ANALISIS OPTIMASI SISTEM TANAM TUMPANGSARI USAHATANI CABAI RAWIT DENGAN SAYURAN DI DESA NGANTRU, KECAMATAN NGANTANG, KABUPATEN MALANG, JAWA TIMU - Eka Purnamasari; Masyhuri Mahfudz; Farida Syakir (Program Studi Agribisnis, 2020)
This study aims to determine the Farm feasibility of each vegetable farming (cayenne pepper, shallots, and mustard greens), and determine the optimization of intercropping farming systems cayenne pepper with vegetables (shallots, mustard greens) and sensitivity value that does not change optimal solution. This research was determined purposively in Ngantru Village, Ngantang District, Malang Regency, East Java. The method used is farm analysis and linear program analysis using the simplex method using LINDO (Linear Interactive Discrete Optimizer) application. The results of the analysis show the average R/C Ratio of cayenne pepper with a planting area of 0.196 ha is 1.6. Average R/C Ratio of mustard greens with a planting area of 0.1453 ha is 1.3. Average R/C Ratio of shallots with a planting area of 0.126 ha is 1.4. Which means that farming is feasible to be cultivated, because R / C Ratio is greater than 1. While the optimization that gets the highest income is optimization model 2 consisting of cayenne pepper plants with shallots, with an optimal income of Rp 21.554.560,00. Optimal producttion of cayenne pepper (x1) is 1,102 kg, and optimal production of shallot (X3) is 1,633 kg. The sensitivity value that does not change the optimal solution is divided into two, namely the range when ther is a change in the coefficient of the objective function to the optimal solution and the range when there is a change in right value of the limiting function on the optimal solution.